Weed control and sustainable rice production through rice intensification system and conventional practices of weed competition periods and age of transplanted seedlings - Muhammad Ather Nadeem; Bilal Ahmad Khan; Asim Riaz Chadar; Rizwan Maqbool; Ali Raza; Muhammad Mansoor Javaid; Athar Mahmood; Muhammad Ishfaq Khan; Masood Ahmad; Muhammad Irfan (Semina: Ciências Agrárias, 2022)
Rice is an important cereal crop of global interest based on its daily uses. It was observed that the average yield of rice is low than its potential production due to the traditional growing techniques and weed intensification. Recently, the rice intensification system (RIS) has emerged as an alternative to the conventional rice cultivation system. A two-year field study was carried out to investigate the impact of seedling age (14, 21 & 28 days) and the weed competition periods (weedy check, 20, 40, 60, 80 DAT and weed-free throughout the growing season) in rice cultivated through RIS.  Weedy check and weed-free for the growing season were kept as a control treatment. The results of our study revealed that a maximum dry weight (108.7 and 111.79 gm-2) and weeds density (101.7 and 110.6 plants m-2) of weed recorded in weedy check plot where 28 days old seedlings was transplanted while minimum dry weight (11.01 and 10.3 gm-2) and weeds density (9.7 and 10.9 m-2) were achieved in plots where 21 days old seedlings were transplanted and remain weed free. It was noted that weed density and weed dry biomass were gradually increased with increasing weed competition period at all ages of the rice seedling. Purple nutsedge (C. rotundus) exhibited maximum relative proportion in total weed’s density and dry biomass and also ranked first by weed summed dominance ratio (WSDR). Agronomic yield and yield contributing traits such as number of fertile tillers per hills (58.1 and 56.0), plant height (130.5 cm and 125.6 cm), kernels per plant (186.4 and 179.4), straw yield (7.8 t ha-1 and 7.5 t ha-1) and kernel yield (5.2 and 5.0 t ha-1) were maximum in plot that remained weed-free throughout the growing season with a seedlings age of 21 days during 2010 and 2011 respectively. Percent yield losses were minimum in plots with 21 days old seedling transplantation and at 20 days of weed competition period. Hence, present study concludes that 21 days old fine rice seedlings should be transplanted and weeds should be controlled within 20 DAT under SRI for effective weed control to avoid yield losses.